Some reflections about the evaluation of the physical condition of women in the climacteric stage (Review) (Revista científica Olimpia, 2019)
This article aims to reflect on the evaluation of physical condition; of physical abilities as a complement to physical condition; of different batteries for evaluation of physical condition; of how the application of batteries of evaluation of physical condition has behaved more in Cuba, highlighting the most used and highlight the importance of the evaluation of the physical condition of women in the climacteric stage. Batteries of tests are analyzed to measure physical condition, which are related to the evaluation of physical condition, where a dichotomy of criteria among its authors is perceived, based on its standardization towards populations from other latitudes with differences in lifestyles, feeding and weather. It is also referred to that it is necessary to analyze certain limitations that currently exist in the methodological and investigative order which affect the evaluative procedures to be applied to women in climacteric stage, because it is still valued from its generality. . The authors who have dealt with the subject of physical condition have done so from different perspectives, focusing their studies on different population groups. Batteries are analyzed for large sectors of the adult population, which cover various generational groups to which identical tests are applied, obviating that the middle-aged woman undergoes biological and psychological changes that are accentuated in the climacteric stage.
Keywords: climacteric; lesspause; physical condition; physical capacities; evaluation; test battery